PENTINGNYA PERKEMBANGAN KOGNITIF PADA ANAK - Ranianisa Rahmi; Desyandri; Irda Murni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Heredity and environment both affect body size (physical development). The continued growth of the brain and nervous system is the most important physical development during early life. However, the child's personality in cognitive form has a significant influence on the child's growth and development, both in character and personality. As a result, the authors hide how cognitive development affects children. With a qualitative descriptive approach, it can be concluded that many factors influence children's cognitive development, but in this case a teacher must have a strategy or effort to overcome each of the factors that affect the child's cognitive development. As a result, a child's process of cognitive development includes progressive learning processes such as attention, memory, and logical thinking. These skills must be developed so that children can process information and learn to judge, analyze, remember, compare, and understand causal relationships. So that adequate training and training can boost children's thinking and learning abilities.